If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7x + 12 = 3(x + 6) Reorder the terms: 12 + 7x = 3(x + 6) Reorder the terms: 12 + 7x = 3(6 + x) 12 + 7x = (6 * 3 + x * 3) 12 + 7x = (18 + 3x) Solving 12 + 7x = 18 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. 12 + 7x + -3x = 18 + 3x + -3x Combine like terms: 7x + -3x = 4x 12 + 4x = 18 + 3x + -3x Combine like terms: 3x + -3x = 0 12 + 4x = 18 + 0 12 + 4x = 18 Add '-12' to each side of the equation. 12 + -12 + 4x = 18 + -12 Combine like terms: 12 + -12 = 0 0 + 4x = 18 + -12 4x = 18 + -12 Combine like terms: 18 + -12 = 6 4x = 6 Divide each side by '4'. x = 1.5 Simplifying x = 1.5
| 8b-20=4 | | 10000.00*0.072= | | 3cos(pix)= | | x+2x-=10 | | 2x+9-4(x+1)=3x+9 | | 9x-2=7x+38 | | 0.3(p+6)-0.8(p+6)=-5 | | 3cos(pi)x= | | 16x(x-2)=(8x-25) | | 0.4x-5=.75x-4 | | 0=6x^4-x^3-7x^2+9x+2 | | 16x-9x=840 | | 10t+5(1.4-t)=8 | | -4x+29= | | 7a+7=14 | | 11x+8x=1862 | | 5x(4x+1)(3x-7)=0 | | 2x+9-4x-4(x+1)=3x+9 | | 12(x+2)=24 | | 5x+2=26-3x | | 4(x-1)=x+6 | | v-(-9)=15 | | m+0.72=1.54 | | 5(n-8)(4n+5)=0 | | 53x-x^2=196 | | X+(x+25)+(x-10)=395 | | 2x-7*0=4 | | 2(6x)+19y=310 | | 25x=35 | | 17=6g-13 | | 4000*x^3=5000 | | 81-2x=9-10x |